Forward Design and Automatic Optimization of Rotor Profile of the Twin Screw Compressor - Sun Weijie; He Xueming; Hu Rong (Jixie chuandong)
At present, there are two ways to design the rotor profile of a twin screw compressor: forward design and reverse design. In the forward design, the first step is to obtain a certain profile of one rotor (female rotor generally). The next is to solve the profile of the other rotor (male rotor generally) based on the law of meshing and the method of coordinate transformation. Further, the meshing line is achieved. In the reverse design, we should obtain the meshing line firstly and then the profiles of rotors are obtained based on the method of coordinate transformation and the law of meshing. This study conducts a research on the forward design of twin screw compressor based on comprehensive performance and tries to deduce a method of automatic optimization. The procedures are as follows: dividing the profiles of rotors into sections, solving the expression of each section, achieving the nodes of each section, making sure the adjustment range of control points of the rotor profile and proceeding the automatic optimization based on comprehensive performance. By comparison, the sealing property of rotor profiles has been improved by automatic optimization.